Functional Construction of Pronouns in Arabic Grammar (ALUSTATH JOURNAL FOR HUMAN AND SOCIAL SCIENCES, 2022)
The construction occupies a large space in the grammar lesson, almost reaching its half, as it is the presumption of parsing and together they constitute the field of grammar. However, syntax occupied the field of fame until it became synonymous with syntax, so syntax was called the science of syntax, and there is no surprise in that. Syntax is a science that specializes in studying the conditions of the end of words in terms of syntax and construction. Since the syntax was more expressive and more beneficial, they made it synonymous with grammar.Grammarians divided Arabic speech in terms of the change of movement of the last of its words and their stability on the expressive and the constructive, so they called the one whose movement changes at the end of it expressive, and the last of which is established on one movement based on, and these two terms were true of the entirety of the words of Arabic speech, but we have hinted in some citizens that the construction limit is not true. On some words, I mean the pronouns that had a different situation in the syntax and construction, so we wanted to shed light on them in this research, Amen to reach a statement of their position in this duality and the function of its construction or syntax, in two topics: the first is in the concept of syntax and construction, and the second is in the specificity of construction In pronouns and their role in their grammatical functions. In the end, let us reach the most important results that we mention in the conclusion. God is the Guardian of success.